PROTECTION OF INSURANCE LAW IN ARBITRATION (TAHKIM) PROCEDURE IN THE TURKISH REPUBLIC - Гезалзаде, Турал Імамалі огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: definition of an alternative system for ensuring the protection of the rights of subjects of insurance relations. Methods of research: analysis and study of the experience of an alternative way of protecting the insurance rights of subjects of insurance legal relations in the Turkish Republic (tahkim). Results: practical utility of introducing the practice of alternative judicial and other in particular, arbitration (non-state) system of protection of the rights of the parties to insurance legal relations was determined in the Republic of Azerbaijan. Discussion: proposal of the use in the practice of insurance legal relations of an alternative system of protection of rights.